Структура родини у другій половині XVIII ст. (на прикладі села Азарівки Стародубського полку) - Якименко, О. І. (НТУ "ХПІ", 2014)
У статті, на підставі статистичних даних, аналізуються загальна чисельність, статевий та поколінний склад, типологія та структура селянських родин, а також показники населеності домогосподарств с. Азарівки Стародубського полку у другій половині XVIII ст. За допомогою системи умовних позначень ілюструється структура кількох родин. В основу дослідження покладена найбільш поширена у сучасній історичній демографії термінологічна та графічна класифікація домогосподарств, розроблена англійським істориком П. Ласлеттом.

Being guided by historical-statistic sources author analyses the dynamics of total number, gender, density of population, generation composition, finds features, typology and structure of peasant family in the village Azarivka of Starodubskiy regiment on the territory of Northern Hetmanshchyna in the second half of XVIII century. With the help of system of shorthand he shows the structure of several peasant families, makes an attempt to study the influence of migratory processes on forming of population structure. On the basis of information author makes comparative analysis with results of studying peasant families in the XVI-XVIII centuries, made by other scientists.
Structure of family in the second half of the 18-th century (on the sample of Azarivka village Starodubskiy regiment)
Keywords: домогосподарство; шлюбна пара; нуклеарна сім'я; розширена сім'я; мультифокальна сім'я; household; conjugal family unit; nuclear family; extended family; multiple family